Pengaruh Interaksi Live Streaming TikTok dan Diskon Khusus terhadap Loyalitas Konsumen melalui Kepuasan Pelanggan sebagai Variabel Intervening - Rada Febrianti; M. Afuan; Deni Saputra (ARZUSIN, 2026)
Although the growth of live commerce through TikTok has expanded the ways consumers obtain information, interact with sellers, and respond to promotions, the relationships between live-streaming interaction, special discounts, and consumer loyalty through customer satisfaction have continued to yield inconsistent results. This study aimed to analyze the effects of TikTok live-streaming interaction and special discounts on consumer loyalty, both directly and through customer satisfaction. The study employed a quantitative approach with an explanatory survey design involving 100 students from the 2022 cohort of the Department of Management at Universitas Putra Indonesia “YPTK” Padang, who were selected using accidental sampling. Data were collected using a Likert-scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares. The results showed that live-streaming interaction had a positive and significant effect on customer satisfaction (β = 0.517; p < 0.001), while special discounts had positive and significant effects on customer satisfaction (β = 0.284; p = 0.003) and consumer loyalty (β = 0.311; p = 0.001). However, live-streaming interaction and customer satisfaction had no direct effects on consumer loyalty, and customer satisfaction did not mediate the effects of either live-streaming interaction or special discounts on consumer loyalty. These findings enrich the application of the Stimulus–Organism–Response framework in the context of live commerce and confirm that promotions offering tangible value play a more direct role in building loyalty than interaction and satisfaction alone. In practical terms, businesses need to combine relevant discounts with responsive interaction, trust, and service quality to build sustainable consumer loyalty.